Strategi Masyarakat Petani Dalam Memenuhi Kebutuhan Keluarga Pasca Erupsi Gunung Marapi di Nagari Aie Angek Kecamatan X Koto Kabupaten Tanah Datar - Pranata, Syahrul; Elfemi, Nilda; Rahmadani, Sri (CV. Rayyan Dwi Bharata, 2025)
This research is motivated by the eruption of Mount Marapi, which has had a significant impact on the environment and the surrounding community. One of the most vulnerable groups affected by the eruption is farmers. The eruption not only damages agricultural land but also significantly affects the socioeconomic conditions of farmers.The impact of Mount Marapi's eruption is particularly severe for communities living around its foothills, especially in areas within a radius of approximately 4 km from the volcano's peak. Nagari Aie Angek is one of the villages in X Koto District, Tanah Datar Regency, West Sumatra Province. However, the village is now covered in thick volcanic ash from Mount Marapi’s eruption.As a result of this disaster, farmers in Aie Angek face several major challenges, including damaged homes, destroyed and unproductive farmland, and a decline in household income. Consequently, the people of Aie Angek must adopt various strategies to meet their daily needs. This study aims to analyze the strategies employed by farming communities to meet their family's needs after the eruption of Mount Marapi in Nagari Aie Angek, X Koto District, Tanah Datar Regency. The research is based on James C. Scott’s Survival Mechanism Theory and uses a qualitative approach with a descriptive type.The sampling technique used in this study is purposive sampling. The data collected consists of both primary and secondary data. The data collection methods include observation, interviews, and document studies. The data analysis follows the approach proposed by Miles and Huberman.The study involves 16 informants, including the Head of Nagari Aie Angek and 15 residents of Nagari Aie Angek who live in Jorong Kandang Sampie and work as farmers. The research findings indicate several general patterns among the farming community of Nagari Aie Angek after the eruption of Mount Marapi, particularly regarding their strategies for meeting their family's needs.Farmers employ three main strategies to sustain their households post-eruption:Selling their assets, Taking loans from banks, and Receiving financial support from their children and relatives.These strategies help affected farmers meet their daily needs. Additionally, the study identifies various challenges faced by farmers in securing their livelihood after the eruption.